Kinematic validation of a human thumb model - Phutane, Uday; Roller, Michael; Björkenstam, Staffan; Linn, Joachim; Leyendecker, Sigrid (Proceedings of the ECCOMAS Thematic Conference on Mutlibody Dynamics, 2017)
The human thumb is a three-link and three-joint multibody system. Two joints resemble a saddle with two degrees of freedom (DoFs) each, while the third joint is a single DoF joint like a revolute. The two DoFs joints have been modeled as universal joints in many biomechanical works, however anatomically they have axes that are non-intersecting and non-orthogonal. These axes enable the thumb to perform complex motions and to produce the necessary thumb tip forces. Our aim is to develop a biomechanical model of the thumb with the anatomically feasible joint setup. To validate the kinematics of the system, we perform two tests. Firstly, we move the thumb by changing the values of all the DoFs through two different ranges of motions, namely the maximum range of motion (RoM) and the grasp RoM. The grasp RoM is smaller than the maximum RoM. Hence, the grasp RoM volume is lesser than the maximum RoM and this volume reduction is a kinematic measure of the thumb, which we compare for five models (with same joint designs but different axes locations and orientations) with data from literature. Further, the rotation around its longitudinal axis of the thumb can be measured for the thumb in different postures. The thumb joints in themselves do not have a rotation DoF around the longitudinal axis. For different postures, we compute this rotation of the thumb, which we compare with data from literature. In both tests, the results obtained from simulation are in close agreement with literature data and consequently the thumb model’s kinematics is validated.
Keywords: humb kinematics; thumb internal rotation; range of motion; point clouds; anatomically variable thumb models.